Mcl‐1 targeting strategies unlock the proapoptotic potential of TRAIL in melanoma cells. Issue 11 (4th September 2020) - Sarif, Zina; Tolksdorf, Beatrice; Fechner, Henry; Eberle, Jürgen
Abstract: TNF‐related apoptosis‐inducing ligand (TRAIL) induces apoptosis selectively in cancer cells. For melanoma, the targeting of TRAIL signaling appears highly attractive, due to pronounced TRAIL receptor expression in tumor tissue. However, mechanisms of TRAIL resistance observed in melanoma cells may limit its clinical use. The Bcl‐2 family members are critical regulators of cell‐intrinsic apoptotic pathways. Thus, the antiapoptotic Bcl‐2 protein myeloid cell leukemia 1 (Mcl‐1) is overexpressed in many tumor types and was linked to chemotherapy resistance in melanoma. In this study, we evaluated the involvement of antiapoptotic Bcl‐2 proteins (Bcl‐2, Bcl‐xL, Bcl‐w, Mcl‐1, Bcl‐A1, and Bcl‐B) in TRAIL resistance. They were targeted by small interfering RNA‐mediated silencing in TRAIL‐sensitive (A‐375, Mel‐HO) and in TRAIL‐resistant melanoma cell lines (Mel‐2a, MeWo). This highlighted Mcl‐1 as the most efficient target to overcome TRAIL resistance. In this context, we investigated the effects of Mcl‐1‐targeting microRNAs as well as the Mcl‐1‐selective inhibitor S63845. Both miR‐193b and S63845 resulted in significant enhancement of TRAIL‐induced apoptosis, associated with decreased cell viability. Apoptosis induction was mediated by caspase‐3 processing as well as by Bax and Bak activation, indicating the critical involvement of intrinsic apoptosis pathways. These data may indicate a high relevance of Mcl‐1 targeting also in melanoma therapy. Furthermore, the data may suggest to consider the use of the tumor suppressor miR‐193b as a strategy for countering TRAIL resistance in melanoma.